On the Contents of the Concept of Ideology - Karosas, Justinas (Problemos, 1977)
The article deals with the methodological basis of the Marxist approaches to the analysis of ideology as of a definite social phenomenon. The author attempts to reveal the objective contents of the concept of ideology. An analysis of the objective historical contents of relations between the individual and society shows that ideology is an inevitable result of the alienation in social relations, which, in its tum, poses a special problem of the adjustment of relations, between the individual and society. In this sense, ideology is defined, as a means by which an objective social interest is realized under the conditions of alienated social relations. The existence of objective prerequisites for the destruction of class society matures objective prerequisites for the establishment of direct relations between the individual and society and for his becoming an actual subject of history, i.e., for the elimination of social alienation. At the same time the social roots of behaviour of the individual in society are revealed. Thus the principles and standards of socialist ideology are given scientific substantiation and are shown as being based on cognized objective necessities of social development.